The Influence of Leadership and Training on Teacher Competence and Performance - Muhammad Syafi'i A Basalamah; Ajmal As'ad; Masruhi Kamidin (Ta'dib: Jurnal Pendidikan Islam, 2022)
This research aims to determine the effect of leadership and education, and training on teacher competence and performance at private Islamic secondary schools (MTSS) in Muhammadiyah Bulukumba Regency. This study uses a quantitative approach. The data used in this study are primary data and secondary data. Primary data was obtained by distributing questionnaires to respondents, the teachers at MTSS Muhammadiyah Bulukumba Regency. Meanwhile, secondary data were obtained from institutions/organizations or parties related to this research, namely data from the MTSS Muhammadiyah Region, Bulukumba Regency, in the form of data on the influence of leadership and training on teacher performance through competence. The sampling technique used in this research is purposive sampling. The analytical method used is path analysis in testing the hypothesis test with the help of PLS 3.0. The results of this study indicate that the leadership and training variables have a positive effect on teacher competence and performance at MTSS Muhammadiyah Bulukumba Regency, and leadership variables affect teacher performance at MTSS Muhammadiyah Bulukumba Regency. The results of this study are used as input for MTSS Muhammadiyah Bulukumba Regency in matters of leadership, training, and competence and their influence on teacher performance, as well as reference material for further researchers who are interested in leadership, training, competence, and teacher performance.